2015
DOI: 10.1111/aos.12914
|View full text |Cite
|
Sign up to set email alerts
|

Hearing in older adults with exfoliation syndrome/exfoliation glaucoma or primary open‐angle glaucoma

Abstract: Purpose To determine if adults, aged 66–96 years, with exfoliation syndrome (XFS)/exfoliation glaucoma (XFG), or primary open-angle glaucoma (POAG) have poorer hearing than controls of similar age. Methods Case (XFS/XFG and POAG) and control status were diagnosed in the Reykjavik Glaucoma Studies (RGS) using slit-lamp examination, visual field testing, and optic disc photographs; the RGS data were merged with the Age, Gene/Environment Susceptibility–Reykjavik Study (AGES-R) that collected hearing data using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 36 publications
0
22
2
Order By: Relevance
“…However, the relationship between glaucoma and hearing loss is controversial. A recent study have reported that patients with pseudoexfoliation syndrome/pseudoexfoliation glaucoma or patients with POAG did not show a significant difference in hearing compared to controls after considering possible confounders [22]. In the present study, visual field impairment confirmed by FDT was more frequent in hearing-impaired group compared to normal hearing group.…”
Section: Discussioncontrasting
confidence: 42%
“…However, the relationship between glaucoma and hearing loss is controversial. A recent study have reported that patients with pseudoexfoliation syndrome/pseudoexfoliation glaucoma or patients with POAG did not show a significant difference in hearing compared to controls after considering possible confounders [22]. In the present study, visual field impairment confirmed by FDT was more frequent in hearing-impaired group compared to normal hearing group.…”
Section: Discussioncontrasting
confidence: 42%
“…Since a prior report found no relation between hearing loss and POAG 29 we included the cochlea as a reference tissue (1797 genes). Using this information we constructed tissue-specific annotation where each SNP within 50kb of the start and end site of the selected genes defined a category.…”
Section: Partitioning Poag and Iop Heritabilitymentioning
confidence: 99%
“…A total of 21 publications were included in the systematic review 4,18,31,39–56 . All studies diagnosed XFS by ophthalmologic examination (i.e., slit‐lamp biomicroscopy and gonioscopy).…”
Section: Resultsmentioning
confidence: 99%
“…Despite the large amount of literature examining XFS, the severity and characteristics of XFS HL and vestibular dysfunction have not been clearly defined. Although several studies found a greater level of HL in patients with XFS compared to controls, the largest case–control study found no discernable evidence for increased sensorineural HL in XFG compared to controls 31 . Therefore, meta‐analysis was warranted to investigate differences between studies.…”
Section: Introductionmentioning
confidence: 99%